Critical Analysis of the Concept of Usury in Islamic Economics and its Implications for Islamic Finance - Rais Abdullah; Sitti Nikmah Marzuki; Yayuk Karliena; A Zulfikar D (Yayasan Adra Karima Hubbi, 2025)
The concept of usury (riba) occupies a pivotal position in Islamic economics, serving as a foundational principle shaping Islamic financial practices. Despite its centrality, the interpretation and application of riba have been subjects of extensive debate among scholars, particularly concerning its implications for modern Islamic finance. This study aims to critically analyze the concept of riba within the framework of Islamic economics, exploring its historical evolution, interpretative nuances, and contemporary challenges. Employing a qualitative methodology, this research integrates a systematic review of classical Islamic jurisprudence texts and modern scholarly discourse, complemented by case studies of Islamic financial institutions. The findings reveal that while riba is unequivocally prohibited in Islamic law, its definition and scope vary, influencing the operational dynamics of Islamic financial products such as murabahah, ijarah, and sukuk. Moreover, the study identifies a tension between theoretical ideals and practical implementations, highlighting the need for greater consistency and innovation in Islamic finance to align with maqasid al-shariah. The study concludes that a nuanced understanding of riba is essential for addressing contemporary financial complexities and fostering the growth of an ethical and sustainable Islamic financial system.